Theoretical Design and First Test in Laboratory of a Composite Visual Servo-Based Target Spray Robotic System - Dongjie Zhao; Ying Zhao; Xuelei Wang; Bin Zhang (Journal of Robotics)
In order to spray onto the canopy of interval planting crop, an approach of using a target spray robot with a composite vision servo system based on monocular scene vision and monocular eye-in-hand vision was proposed. Scene camera was used to roughly locate target crop, and then the image-processing methods for background segmentation, crop canopy centroid extraction, and 3D positioning were studied. Eye-in-hand camera was used to precisely determine spray position of each crop. Based on the center and area of 2D minimum-enclosing-circle (MEC) of crop canopy, a method to calculate spray position and spray time was determined. In addition, locating algorithm for the MEC center in nozzle reference frame and the hand-eye calibration matrix were studied. The processing of a mechanical arm guiding nozzle to spray was divided into three stages: reset, alignment, and hovering spray, and servo method of each stage was investigated. For preliminary verification of the theoretical studies on the approach, a simplified experimental prototype containing one spray mechanical arm was built and some performance tests were carried out under controlled environment in laboratory. The results showed that the prototype could achieve the effect of “spraying while moving and accurately spraying on target.”